Kalanchoe ×gildenhuysii (Crassulaceae subfam. Kalanchooideae), a new nothospecies derived from K. millotii and K. tomentosa - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2020)
The majority of the species of Kalanchoe Adanson (1763: 248) in cultivation in, especially, mild-climate parts of the world originates from Madagascar, a present-day centre of high species diversity for the genus (Gehrig et al. 2001; Descoings 2003; Smith & Figueiredo 2018). Of 45 species, hybrids, and cultivars of Kalanchoe listed by Springate (1995: 178–185) as being cultivated in Europe, both out-of-doors and under glass, 29 ( 64%) are either from Madagascar or are based on material originally collected from that country, with the remaining 16 being mainly from eastern and southern Africa, as well as from the Middle East, Socotra, India, and east Asia.